Analgesic Effect of Ziziphus abyssinica Involves Inhibition of Inflammatory Mediators and Modulation of KATP Channels, Opioidergic and Nitrergic Pathways - Henneh, Isaac Tabiri; Armah, Francis Ackah; Ameyaw, Elvis Ofori; Biney, Robert Peter; Obese, Ernest; Boakye-Gyasi, Eric; Adakudugu, Emmanuel Awintiig; Ekor, Martins (Frontiers in Pharmacology, 2021)
The diversity offered by natural products has timelessly positioned them as a good source for novel therapeutics for the management of diverse medical conditions, including pain. This study evaluated hydro-ethanolic root bark extract of Ziziphus abyssinica (ZAE) as well as β-amyrin and polpunonic acid isolated from the plant for analgesic property. The study also investigated the mechanism responsible for this action in the extract. The antinociceptive potential of ZAE (30, 100, and 300 mg/kg, p.o.) was assessed using the tail-immersion test (TIT), acetic acid-induced writhing test (AAT), and formalin test (FT). The extract’s effect on acute and chronic musculoskeletal pain was also assessed by administering carrageenan unilaterally into the rat gastrocnemius muscles and measuring pain at 12 h and 10 days for acute and chronic pain respectively. The involvement of pro-inflammatory mediators (prostaglandin E2, bradykinin, TNF-α, and IL-1β) was assessed. The possible pathways mediating the observed analgesic effect of ZAE were further assessed using the antagonists: naloxone, glibenclamide, NG-L-nitro-arginine methyl ester (L-NAME), atropine, nifedipine, and yohimbine in the FT Also the analgesic effect of two triterpenoid compounds, β-amyrin, and polpunonic acid, previously isolated from the plant was assessed using the TIT. The anti-nociceptive activity of ZAE was demonstrated in the TIT by the significant (p<0.05) increase in tail withdrawal threshold in ZAE-treated mice. ZAE also markedly reduced writhing and paw licking responses in both AAT and FT and significantly (p<0.05) attenuated both acute and chronic musculoskeletal pain. ZAE also significantly reversed hyperalgesia induced by intraplantar injection of PGE2, bradykinin, TNF-α, and IL-1β. Furthermore, data revealed the involvement of opioidergic, ATP-sensitive K+ channels and NO-cGMP pathways in the analgesic effect of ZAE. Both β-amyrin and polpunonic acid exhibited analgesic activity in the tail suspension test. Our study demonstrates ZAE as an important source of new therapeutic agents for pain management.